The Relationship Between Serum Angiogenic Factor Levels and Disease Activity in Rheumatoid Arthritis - Zahide ASLANALP; Canan TIKIZ; Aslıhan ULUSOY; Şebnem ORGUC; Aysun BİLGİ YEDEKCİ and Cevval ULMAN (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the relationship between serum angiogenic factor levels and disease activity in patients with rheumatoid arthritis (RA) using both clinical and dynamic wrist magnetic resonance imaging (MRI) data. Patients and methods: Simultaneous serum angiogenesis markers [vascular endothelial growth factor (VEGF), angiopoietin-1 (ANG1), ANG2, and tyrosine-protein kinase receptor for angiopoietin (Tie-2)] were studied in 40 patients with RA (13 males, 27 females; mean age 51.1±10.8 years; range, 23 to 69 years) and 20 healthy controls (11 males, 9 females; mean age 47.3±12.8 years; range, 29 to 69 years) and dynamic contrast-enhanced wrist MRI was performed in 40 RA patients and seven controls. Rate of early in 55th second (REE) and Relative enhancement (REt) values were calculated from the signal time curve values obtained from the analysis of images. In clinical assessment, duration of morning stiffness, patient pain assessment [visual analog scale (VAS)], physician and patient global assessments (VAS) were recorded. The number of tender joints and swollen joints were determined. Disease activity score 28 and Ritchie scores were calculated. Health assessment questionnaire was used for functional evaluation. Anti-cyclic citrullinated peptide, rheumatoid factor, erythrocyte sedimentation rate and high sensitive C-reactive protein analyses were performed. Results: Serum VEGF, REE and REt values were significantly higher in RA patients than healthy controls (p=0.002, p=0.00, p=0.00, respectively). There was no significant correlation between serum angiogenesis markers and clinical parameters or REE and REt (p>0.05). VEGF value correlated positively with disease duration (p=0.024). Conclusion: Serum VEGF was higher in RA patients. While its level was associated with disease duration, no significant correlation was found with disease activity. As a diagnostic test, dynamic contrast-enhanced MRI was a valuable method for showing disease activity.